Psychometric evaluation of the Finnish translation of the assessment of communication and interaction skills (ACIS-FI). (17th February 2020) - Fan, Chia-Wei; Keponen, Riitta; Piikki, Sanna; Tsang, Hector W. H.; Popova, Evguenia S.; Taylor, Renee
Abstract: Background: The Model of Human Occupation (MOHO) is a widely used conceptual practice model in Finland. Therefore, Finnish translations of valid and reliable MOHO assessments are needed. Objective: The primary objective of this study was to examine the psychometric properties of the Finnish translation of the Assessment of Communication and Interaction Skills (ACIS-FI) using the many-facet Rasch model approach. Methods and Materials: Twenty-eight occupational therapists completed an in-person training workshop on the ACIS-FI and participated as raters in this study. One hundred and forty-eight clients were rated using the ACIS-FI. Rating scale functioning, unidimensionality, person validity and rater severity, item targeting, and item and person separation statistics were examined. Results: The rating scales demonstrated adequate functioning; the rating category 'deficit' was infrequently adopted by the raters. The ACIS-FI had satisfactory construct validity, as confirmed by all items exhibiting unidimensionality within a single construct (i.e. communication and interaction skills), and appropriate item fit. Validity was further confirmed through low person misfit (6%) and low rater misfit (3.6%). No ceiling or floor effects were found. The ACIS-FI was able to separate clients into four levels of communication and interaction skills. Conclusions: This study offers evidence for the validity of the ACIS-FI as a measure of communication and interaction skills in occupational therapy. Significance: The ACIS-FI offers Finnish practitioners and researchers a valid tool to measure communication and interactions skills that is theoretically grounded in the MOHO.